Emotion in Group Decision and Negotiation - Martinovski, Bilyana (Springer, 2015)
The volume offers an exploration of methods for analysis of emotion in negotiation, such as cognitive modeling, discourse analysis, all testing, subsequent multidimensional scaling, impression rating, and graph modeling for conflict resolution, reasonable and unreasonable disagreement.